Perilaku Korupsi di Indonesia: Tinjauan Teoritik Model MARS - Kandung Sapto Nugroho (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2020)
Corruption behavior is not a culture. Culture is a positive value. Corruption behavior is a negative value, so corruption is not a culture. Many factors cause corruption to flourish in Indonesia, so from year to year it is difficult to eradicate it. This study tries to identify the causes or conditions underlying corruption in Indonesia. The method used in this study is Systematic Liteature Review (SLR), which is by identifying, assessing, and interpreting all findings on a research topic to answer the research questions that have been previously determined. The results of a theoretical study that individual behavior will be influenced by four things, namely motivation, ability, role perceptions, and situational factors, abbreviated as MARS. The conclusion of this theoretical study is that corruption behavior is the output of an individual's thinking system as a counterproductive behavior that is formed due to individual character factors and organizational culture's contribution. So eradicating corrupt behavior must be intervened with policies that focus on forming / motivating motivators, employee up-grading abilities, clarity of the role of individuals in the organization and system improvement, organizational culture that encourages employees to perform better.